Proposal for a UK domestric water trading scheme. - Griggs, John; Jeffrey, Paul (Thomas Telford, 2007)
Water charges in the UK, Ireland, Canada and parts of the USA are largely based upon house value rather than consumption. This paper shows how charges based upon consumption could facilitate trading among metered consumers and provide incentives to non-metered customers to switch to a metered tariff. To develop a household domestic water trading scheme, various environmental trading schemes were examined including the EU emissions trading scheme (EU ETS) and tradable energy quotas (TEQs). The derived scheme encourages domestic consumers to trade and reduce their water use. Although a degree of trading would be possible on an occasional basis for unmetered properties (by the substitution of appliances with water-conserving models) and conventionally metered properties (based upon sustained reductions in consumption, but on an annual basis), frequent full trading would only be possible if smart water meters were installed. It is concluded that, while water trading schemes are feasible, they present a number of challenges. However, due to the availability of a number of existing potential elements, implementation—at least on a regional basis—could be achievable relatively quickly. Once an initial scheme is running it could be refined and expanded to other regions, and nationally or internationally, if appropri
Keywords: Business; Conservation; Hydrology and water resource